ANALISIS DISIPLIN KERJA PEGAWAI PADA KANTOR CAMAT TENAYAN RAYA KOTA PEKANBARU - Nur Khasanah; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Position and role of the Civil Service is important in the administration of government and development tasks as stipulated in Government Regulation No. 53 of 2010 about the Discipline of Civil Servants. Discipline of Civil Servant at the Distric Office of Tenayan Raya Pekanbaru is still said has not gone well. This is caused by the lack of socialization about the importance of employment discipline, lack of strict sanctions for employee indisciplinary, and lack of supervision of work discipline employees. Based on this, researchers conducting of the analysis work discipline of Civil Servants at the Distric Office of Tenayan Raya Pekanbaru. Problems in this research are how the analysis work discipline of the Civil Servants at the Distric Office of Tenayan Raya Pekanbaru and the factors that affect discipline of employees working of Civil Servants at the Distric Office of Tenayan Raya Pekanbaru. This research uses the concept of discipline theory Civil Servant of Hasibuan 2011. The research model in this research is a qualitative descriptive method with data collection through observation and interviews, which the relevant parties in the implementation work discipline at the Distric Office of Tenayan Raya Pekanbaru as the research informants. The result of this reaserch work discipline of the Civil Servants at the Distric Office of Tenayan Raya Pekanbaru has not gone well, this is because the purpose of which was given to the employee are still not in accordance with ability of employees, exemplary leadership the less competent, human relationships are not in harmony, the lack of fairness for the compensation, supervision, and law sanctions, as well as firmness in giving assistance work discipline is not in accordance with the prescribed rules. As for the factors that influence work discipline employees is the lack of good communication in cooperation, the workplace environment is less comfortable, and lack of awareness as the resource implementing discipline.Keywords: Management Human Resources, Work Discipline